Light Scattering by a Subwavelength Plasmonic Array: Anisotropic Model - Anton Nemykin; Leonid Frumin; David Shapiro (Sensors, 2022)
We calculate the light transmission by a subwavelength plasmonic array using the boundary element method for parallel cylinders with different cross-sections: circular or elliptic with axis ratio 4:1. We demonstrate that plasmonic resonance is sharper for the case of horizontal ellipses. This structure is susceptible to refractive index variations in the media since the high derivatives of reflection and transmission coefficients are near the angle of total internal reflection. To obtain an approximate analytical expression, we used the model of a metallic layer. We explore the “sandwich” structure with an anisotropic film between two dielectrics and demonstrate its quantitative agreement with numerical results.